Are noise and air pollution related to the incidence of dementia? A cohort study in London, England - Carey, Iain M; Anderson, H Ross; Atkinson, Richard W; Beevers, Sean D; Cook, Derek G; Strachan, David P; Dajnak, David; Gulliver, John; Kelly, Frank J (BMJ open, 2018)
ObjectiveTo investigate whether the incidence of dementia is related to residential levels of air and noise pollution in London.DesignRetrospective cohort study using primary care data.Setting75 Greater London practices.Participants130 978 adults aged 50–79 years registered with their general practices on 1 January 2005, with no recorded history of dementia or care home residence.Primary and secondary outcome measuresA first recorded diagnosis of dementia and, where specified, subgroups of Alzheimer’s disease and vascular dementia during 2005–2013. The average annual concentrations during 2004 of nitrogen dioxide (NO2), particulate matter with a median aerodynamic diameter ≤2.5 µm (PM2.5) and ozone (O3) were estimated at 20×20 m resolution from dispersion models. Traffic intensity, distance from major road and night-time noise levels (Lnight) were estimated at the postcode level. All exposure measures were linked anonymously to clinical data via residential postcode. HRs from Cox models were adjusted for age, sex, ethnicity, smoking and body mass index, with further adjustments explored for area deprivation and comorbidity.Results2181 subjects (1.7%) received an incident diagnosis of dementia (39% mentioning Alzheimer’s disease, 29% vascular dementia). There was a positive exposure response relationship between dementia and all measures of air pollution except O3, which was not readily explained by further adjustment. Adults living in areas with the highest fifth of NO2 concentration (>41.5 µg/m3) versus the lowest fifth (<31.9 µg/m3) were at a higher risk of dementia (HR=1.40, 95% CI 1.12 to 1.74). Increases in dementia risk were also observed with PM2.5, PM2.5 specifically from primary traffic sources only and Lnight, but only NO2 and PM2.5 remained statistically significant in multipollutant models. Associations were more consistent for Alzheimer’s disease than vascular dementia.ConclusionsWe have found evidence of a positive association between residential levels of air pollution across London and being diagnosed with dementia, which is unexplained by known confounding factors.